Oscillatory Pattern of Sympathetic Nerve Bursts Is Associated With Baroreflex Function in Heart Failure Patients With Reduced Ejection Fraction - Toschi-Dias, Edgar; Montano, Nicola; Tobaldini, Eleonora; Trevizan, Patrícia F.; Groehs, Raphaela V.; Antunes-Correa, Ligia M.; Nobre, Thais S.; Lobo, Denise M.; Sales, Allan R. K.; Ueno-Pardi, Linda M.; de Matos, Luciana D. N. J.; Oliveira, Patrícia A.; et al. (Frontiers in Neuroscience, 2021)
Sympathetic hyperactivation and baroreflex dysfunction are hallmarks of heart failure with reduced ejection fraction (HFrEF). However, it is unknown whether the progressive loss of phasic activity of sympathetic nerve bursts is associated with baroreflex dysfunction in HFrEF patients. Therefore, we investigated the association between the oscillatory pattern of muscle sympathetic nerve activity (LFMSNA/HFMSNA) and the gain and coupling of the sympathetic baroreflex function in HFrEF patients. In a sample of 139 HFrEF patients, two groups were selected according to the level of LFMSNA/HFMSNA index: 1) Lower LFMSNA/HFMSNA (lower terciles, n = 46, aged 53 ± 1 y) and 2) Higher LFMSNA/HFMSNA (upper terciles, n = 47, aged 52 ± 2 y). Heart rate (ECG), arterial pressure (oscillometric method), and muscle sympathetic nerve activity (microneurography) were recorded for 10 min in patients while resting. Spectral analysis of muscle sympathetic nerve activity was conducted to assess the LFMSNA/HFMSNA, and cross-spectral analysis between diastolic arterial pressure, and muscle sympathetic nerve activity was conducted to assess the sympathetic baroreflex function. HFrEF patients with lower LFMSNA/HFMSNA had reduced left ventricular ejection fraction (26 ± 1 vs. 29 ± 1%, P = 0.03), gain (0.15 ± 0.03 vs. 0.30 ± 0.04 a.u./mmHg, P < 0.001) and coupling of sympathetic baroreflex function (26 ± 3 vs. 56 ± 4%, P < 0.001) and increased muscle sympathetic nerve activity (48 ± 2 vs. 41 ± 2 bursts/min, P < 0.01) and heart rate (71 ± 2 vs. 61 ± 2 bpm, P < 0.001) compared with HFrEF patients with higher LFMSNA/HFMSNA. Further analysis showed an association between the LFMSNA/HFMSNA with coupling of sympathetic baroreflex function (R = 0.56, P < 0.001) and left ventricular ejection fraction (R = 0.23, P = 0.02). In conclusion, there is a direct association between LFMSNA/HFMSNA and sympathetic baroreflex function and muscle sympathetic nerve activity in HFrEF patients. This finding has clinical implications, because left ventricular ejection fraction is less in the HFrEF patients with lower LFMSNA/HFMSNA.